THE NUMBER OF HOMOLOGS OF SOME ENZYMES IN THE TRYPTOPHAN BIOSYNTHESIS PATHWAY CORRELATES WITH THE PROPORTION OF PROTEINS ASSOCIATED WITH TRANSCRIPTION IN PLANTS - I. I. Turnaev; I. R. Akberdin; V. V. Suslov; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
The tryptophan biosynthesis pathway (TBP) is ubiquitous in most known organisms, being absent only from animals and some bacteria. It is conserved in plants, although various species differ in the number of TBP enzyme paralogs. In the current work we investigated a putative possible role of changes in the number of paralogs of TBP enzymes in the course of plant evolution. We identified TBP enzyme paralogs in plant species with fully sequenced genomes and estimated the relationship between its number and organismal complexity. It is shown that organismal complexity significantly correlates with the total number of TBP paralogs and for some enzymes specifically (ASA/ASB, PAI, and IGPS). We suggest that such a relationship arises because both organismal complexity and the increasing number of paralogs may be important for the evolutionary adaptation of land plants to variable environmental conditions.